محاكاة الخصائص الإشعاعية التي تؤثر على الحركية الذرية: تطبيق لبعض العمليات الأولية لبلازما ساخنة. - ليفة, أمال (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: الهدف من هذا العمل معرفة مدى تأثير دوال توزيع الطاقة على حساب معدلات التأين وذلك من خلال دراسة معدل التأين بواسطة تصادم الإلكترون داخل البلازما الساخنة وتطبيقه على ذرات والأيونات انطلاقا من التعرف على مختلف الأليات الذرية الأساسية التي تحدث في البلازما من بينها عملية التأين بالتصادم الإلكتروني وهي من أهم النماذج التصادمية الإشعاعية الذرية. تم حساب المقاطع الفعالة للتأين بواسطة برنامج FAC للأيونات الشبيهة بالهيليوم وكذلك تم حساب معدلات التأين بواسطة برنامج حساب العددي بدلالة المقاطع الفعالة المحسوبة ((FAC و باستخدام دوال توزيع الطاقة عن طريق دالة توزيع الغير الماكسويلي لبعض الأيونات الشبيهة بالهيليوم: +Be2+, Li. بالمقارنة بين النتائج المتحصل عليها لمقاطع الفعالة للتأين هناك اتفاقا جيدا أما بالنسبة لمعدلات التأين بالتأثير الإلكتروني وجدنا أن دوال توزيع الطاقة الإلكترون ونسبة الإلكترونات الساخنة fhot تؤثر في حساب معدل التأين. The aim of this work is to know the extent to which the functions of energy distribution affect the calculation of ionization rates by studying the ionization rate by the collision of the electron inside the hot plasma and its application to atoms and ions based on the identification of various basic atomic mechanisms that occur in plasma, including the process of ionization by electronic collision, which is one of the most important models of atomic radiation collision. The effective ionization sections were calculated using the FAC program for helium-like ions, as well as the ionization rates were calculated by the numerical calculation program in terms of the calculated effective sections (FAC) and using energy distribution functions via the non-maxwellian distribution function for some helium-like ions: Be2+, ​​Li+. Comparing the results obtained for effective ionization sections, there is good agreement. As for the ionization rates by the electronic effect, we found that the electron energy distribution functions and the hot electrons ratio fhot affect the ionization rate calculation.
أطروحة دكتوراه تخصص فيزياء تطبيقية في العلوم الدقيقة
Keywords: التأين بالتصادم الإلكتروني، المقاطع الفعالة للتأين، معدل التأين، برنامج FAC ، دوال توزيع الطاقة الإلكترون.; Electron collision ionization, ionization effective sections, ionization rate, FAC program, electron energy distribution functions